The role and effect of aeration on combined demulsification process for stubborn water-in-oil emulsion from slop oil tank - Bhaskoro, P.T. (Asian Research Publishing Network, 2016)
Various demulsification methods have been proposed and reported in literatures to solve water-in-oil (W/O) emulsion. Nevertheless, there is a case where demulsification process cannot break the emulsion 100. The process left behind some amount of rag layer (stubborn emulsion) with greater stability than the original emulsion. Common combined demulsification method (heating, demulsifier injection, and gravity settling) is found ineffective to give expected residence time. Therefore, the work aims to propose aeration into the combined demulsification method for better separation efficiency and as a cheap alternative to solve the stubborn emulsion. The effects of the combination methods are investigated through a designed experiment. The best operating conditions are identified through an optimization using Design Expert software. The optimization goals are to maximize oil recovery and water separation, to minimize the rag layer and to reduce the demulsification cost. Based on the results, the best operating condition is at â42Â°C with injection of 200 ppm chemical demulsifier and â73 cc/min. of aeration rate. The solution was able to provide 58.23 of oil separation fraction with only 12.42 rag layer within 30 min. The demulsification cost is as low as US0.13/barrel. Â© 2006-2016 Asian Research Publishing Network (ARPN).